Modeling and optimization of the orange leaves oil extraction process by microwave-assisted hydro-distillation : the response surface method based on the central composite approach (RSM-CCD model) - Dao, Tan Phat; Nguyen, Duy Chinh; Tran, Thien Hien; Thinh, Phan Van; Hieu, Vu-Quang; Vo, Dai-Viet N.; Nguyen, Trinh Duy; Bach, Long Giang (Rasayan Journal of Chemistry, c/o Dr. Pratima Sharma, 2019)
Although being a by-product after the harvest, orange leaves could be used to produce essential oil through extraction. Application of the essential oil extracted from orange leaves is diverse ranging from food flavoring to cosmetics. This study aimed to develop optimal conditions for microwave assisted hydro-distillation of essential oil from orange leaves. The selected optimization method is Response Surface Methodology in conjunction with the central composite experiment design. The factors that were varied for the production of the orange leaves oil extraction were material-to-water ratio, extraction time, and microwave power. Accordingly, a statistical model was established and Analysis of variance (ANOVA) was carried out to identify the set of factors that gives the highest essential oil yield. Optimization results revealed optimal conditions as follows, material and water ratio of 3.46:1 (mL/g), extraction time of 100.47 min and operating power of 471.58 W. These conditions correspond to the essential oil yield of 0.43% with 92.1 % reliability. In addition, we also analyze the produced essential oils by gas chromatography-mass spectrometry (GC-MS). The GC-MS results revealed that major components of essential oil were Sabinene (30.556 %), Cis-Ocimene (10.139 %), and D-Limonene (9.682 %).